2011
DOI: 10.1177/194277511100600509
|View full text |Cite
|
Sign up to set email alerts
|

Breaking News: Utilizing Video Simulations to Improve Educational Leaders' Public Speaking Skills

Abstract: This article examines specific uses of video simulations in one educational leadership preparation program to advance future school and district leaders' skills related to public speaking and participation in televised news interviews. One faculty member and two advanced educational leadership candidates share their perspectives of several applications of advanced technologies, including one-on-one video simulations with the instructor and collaborative peer review of video portfolios. Finally, the authors pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…Simulations of leadership situations have also been popular in preparation programs. Friend et al (2011) described their use in developing persuasive speech skills and in dealing effectively with the media. Other descriptive research has demonstrated simulations used to develop decision-making skills (Mann et al, 2011).…”
Section: Program Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations of leadership situations have also been popular in preparation programs. Friend et al (2011) described their use in developing persuasive speech skills and in dealing effectively with the media. Other descriptive research has demonstrated simulations used to develop decision-making skills (Mann et al, 2011).…”
Section: Program Elementsmentioning
confidence: 99%
“…The major pedagogies examined in the literature are multimedia methods, cases, simulations, technology, action research, and reflection. Several descriptive studies examined how the use of multimedia tools can enhance social justice (Boske, 2011), public speaking and media communication skills (Friend, Adams, & Curry, 2011), and leadership identity (Guajardo et al, 2011).…”
Section: Pedagogymentioning
confidence: 99%
“…Researchers have highlighted the importance of reflecting individual needs and goals in leadership development programs by considering principals' development stages and inquiry goals (Drago-Severson, 2009;Kegan and Lahey, 2009). In addition, studies have suggested that effective leadership development programs are work related, problem based, and situation driven (Davis et al, 2013;Friend et al, 2011;Mann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In an example from an educational leadership program, doctoral candidates in one program engaged in a simulated television news interview pertaining to a school crisis scenario using a professional camera, lights, and lavalier microphone to develop media and public relations skills (Friend, Adams, & Curry, 2011). The video interviews became part of each candidate’s digital video portfolio, with feedback provided from the instructor and peer group sessions at the end of the course.…”
Section: Framing the Frameworkmentioning
confidence: 99%
“…Adding podcasts to my written communication has helped me reach a stakeholder population well versed in technology and eager to receive information in this format. (Friend et al, 2011, p. 241)…”
Section: Framing the Frameworkmentioning
confidence: 99%